IMPLEMENTASI MODUL TENTANG KITA TERHADAP PENYIAPAN KEHIDUPAN BERKELUARGA BAGI REMAJA - Saiful; Ode, Samsul (Jurnal Governansi, 2024)
This research focuses on implementing the "Tentang Kita" program to prepare family life for adolescents aged 15-24. It was conducted by the Regional Office of Child Empowerment and Population Control in DKI Jakarta Province from 2021 to 2022. The research methodology used is qualitative research. The study draws on Edwards III's ideas regarding the success of policy implementation. It is concluded that the implementation of the "Tentang Kita" program has been successfully carried out, as indicated by the reduction in early marriages in DKI Jakarta Province during 2021-2022. The following factors contributed to the success. (1) Communication and socialization efforts were conducted effectively and maximized communication intensity. (2) Resources: The human resources involved in the program align with the extensive coverage of the program's target areas in DKI Jakarta Province. However, the facilities and funding are still insufficient to support the implementation process of the "Tentang Kita" program. (3) Disposition: Program organizers and facilitators carried out the program according to their capacities. (4) Bureaucratic Structure: The employees of the Department of Child Empowerment and Population Control in DKI Jakarta Province demonstrated a positive attitude, and the operational procedures used by the organizers were easily understood.